Water vapor passing through asphalt mixtures under different relative humidity differentials. (20th March 2018) - Luo, Rong; Liu, Ziyao; Huang, Tingting; Tu, Chongzhi
Highlights: Designed experiments for Phase II water vapor diffusion under 8 RH differentials. Identified a linear relationship between RH differential and diffusion flux. Demonstrated that Phase II water vapor diffusion followed Fick's first law. Proved Phase II water vapor diffusivity independent of RH differential. Revealed much larger water vapor diffusivities in Phase II than those in Phase I. Abstract: Water vapor diffusion in a newly constructed asphalt pavement consists of water vapor accumulating toward the asphalt layer (Phase I) and water vapor passing through the asphalt layer (Phase II). The water vapor diffusion in Phase I under different relative humidity (RH) differentials has been investigated and can be found elsewhere in literature. However, it remains unclear whether the RH differential would affect the diffusion flux and diffusivity of the water vapor passing through the asphalt layer in Phase II. This study investigated the Phase II water vapor diffusion in asphalt mixtures under a variety of RH differentials. Experimental setups were designed and assembled for the Phase II water vapor diffusion experiments. Distilled water, saturated MgCl2 solution, saturated NaBr solution, and saturated KCl solution were stored in containers to provide the RH level of 100%, 36.5%, 62%, and 87%, respectively, under the asphalt mixture specimens that were sealed on top of these containers. The experimental setups were conditioned in environmental chambers to maintain a constant test temperature of 20 ± 0.5 °C and specific RH levels to establish the RH differentials between the air above and below the asphalt mixture specimen. The weight loss of the experimental setup was monitored three times a day using a high-precision scale. A linear relationship was identified between the RH differential and the diffusion flux of the water vapor in Phase II diffusion, which demonstrated that the Phase II water vapor diffusion followed Fick's first law of diffusion. The calculated water vapor diffusivities in Phase II diffusion were significantly larger than those in Phase I diffusion and were independent of the variation of the RH differential between the air above and below the asphalt mixture specimen.